CR-MDC: A Method of Constrained Route for Avoiding Congestion of the Satellite Sensor Network for Agriculture - Yuanyuan Zhang; Jing Wu; Hao Jiang; Jianguo Zhou; Xiuhong Li; Laitao Zhu; Zijing Cheng (International Journal of Distributed Sensor Networks)
In recent years, wireless sensor networks have been widely employed in monitoring agriculture. With social development, large-scale agriculture monitoring by satellite sensor network attracts increasing concerns as well as the transmission problem of plentiful agriculture data. In this paper, we propose a new method of constrained route based on the metric of delay and capacity (CR-MDC) to find route path in satellite sensor network, with the aim of achieving congestion avoidance of network for transferring a large amount of data while monitoring large-scale agriculture. We model the rosette constellation network according to network characteristics through a discrete-time figure and formulate the scheme as a binary integer programming problem in consideration of time-variant parameters, for example, link capacity and link delay. The performance of the constrained route algorithm is compared with the Dijkstra-based routing protocols proposed in existing literature. Moreover, an improved CR-MDC under a route similarity constraint is developed to reduce the handoff times in adjacent slots. Simulation results show that the proposed scheme exhibits lower blocking probability and maximum link utilization but higher average network delay than Dijkstra-based routing while the improved CR-MDC has a higher route similarity than CR-MDC.